Ecological economics an introduction - Common, Michael; Stagl, Sigrid; Common, Mick (Cambridge Cambridge University Press, 2005)
Taking as its starting point the interdependence of the economy and the natural environment, this book provides a comprehensive introduction to the emerging field of ecological economics. The authors, who have written extensively on the economics of sustainability, build on insights from both mainstream economics and ecological sciences. Part I explores the interdependence of the modern economy and its environment, while Part II focuses mainly on the economy and on economics. Part III looks at how national governments set policy targets and the instruments used to pursue those targets. Part IV examines international trade and institutions, and two major global threats to sustainability - climate change and biodiversity loss. Assuming no prior knowledge of economics, this textbook is well suited for use on interdisciplinary environmental science and management courses. It has extensive student-friendly features including discussion questions and exercises, keyword highlighting, real-world illustrations, further reading and website addresses.
Keywords: Ecology -- Economic aspects; Sustainable development; Economics; Environmental sciences; Renewable energy sources